2022
DOI: 10.3390/metabo12020143
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides/Glucose Index Is Associated with Sperm Parameters and Sperm DNA Fragmentation in Primary Infertile Men: A Cross-Sectional Study

Abstract: Study question: we aimed to investigate the relationship between the tyg index and both semen and hormonal characteristics in a cohort of primary infertile men. Summary answer: almost one in two primary infertile men presented with a triglycerides/glucose index (tyg) suggestive of insulin resistance (ir). overall, patients with tyg suggestive of ir showed worse clinical, hormonal, and semen parameters. What is already known: male factor infertility (MFI) is often associated with metabolic disorders such as dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
1
8
1
Order By: Relevance
“…37 A higher TyG index was also associated with more serious sperm DNA fragmentation (OR = 1.92, 95% CI = 1.2, 2.9) and a higher risk of nonobstructive azoospermia (OR = 1.78, 95% CI = 1.1, 2.8). 38 However, the results of ROC analysis indicated that the TyG index was inferior to HOMA-IR in predicting testosterone deficiency occurrence in NHANES participants, which was not in accordance with a previous study carried out on 4299 Chinese men. 39 The reason for this discordance was not clear, but it might derive from different population settings, races, or laboratory protocols.…”
Section: -2014 and 2015-2016 Assessed The Relationship Between Thecontrasting
confidence: 67%
See 1 more Smart Citation
“…37 A higher TyG index was also associated with more serious sperm DNA fragmentation (OR = 1.92, 95% CI = 1.2, 2.9) and a higher risk of nonobstructive azoospermia (OR = 1.78, 95% CI = 1.1, 2.8). 38 However, the results of ROC analysis indicated that the TyG index was inferior to HOMA-IR in predicting testosterone deficiency occurrence in NHANES participants, which was not in accordance with a previous study carried out on 4299 Chinese men. 39 The reason for this discordance was not clear, but it might derive from different population settings, races, or laboratory protocols.…”
Section: -2014 and 2015-2016 Assessed The Relationship Between Thecontrasting
confidence: 67%
“…reported that the TyG index could be used as a predictive marker of unfavorable prognostic factors of radical prostatectomy 37 . A higher TyG index was also associated with more serious sperm DNA fragmentation (OR = 1.92, 95% CI = 1.2, 2.9) and a higher risk of nonobstructive azoospermia (OR = 1.78, 95% CI = 1.1, 2.8) 38 . However, the results of ROC analysis indicated that the TyG index was inferior to HOMA‐IR in predicting testosterone deficiency occurrence in NHANES participants, which was not in accordance with a previous study carried out on 4299 Chinese men 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, for the definition of CKD, we used the threshold set by the KDIGO guidelines (i.e., defining kidney function impairment as eGFR < 90 mL/min per 1.73 m 2 and CKD as eGFR < 60 mL/min per 1.73 m 2 ); however, evidence exists that the threshold for CKD should be set at higher eGFR levels for younger individuals, 41 thus potentially increasing the proportion of men with initial kidney function impairment among young men with primary infertility. Finally, although an association between impaired renal function and semen parameters was not observed, we did not examine alterations in the sperm quality profile that could be even more sensitive to alterations in the state of overall men's health, such as an increase in the percentage of sperm DNA fragmentation 42–44 . In addition, we included a very selected group of infertile men, that is, those with availability of eGFR evaluation in a tertiary referral center; therefore, the study of association of putative risk factors such as impaired kidney function with impaired semen analysis might be biased by information and selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although an association between impaired renal function and semen parameters was not observed, we did not examine alterations in the sperm quality profile that could be even more sensitive to alterations in the state of overall men's health, such as an increase in the percentage of sperm DNA fragmentation. [42][43][44] In addition, we included a very selected group of infertile men, that is, those with availability of eGFR evaluation in a tertiary referral center; therefore, the study of association of putative risk factors such as impaired kidney function with impaired semen analysis might be biased by information and selection bias. Further studies with larger cohorts are certainly needed.…”
Section: Discussionmentioning
confidence: 99%
“…According to Belladelli F et al [ 23 ], the TyG index is calculated as ln [triglycerides (mg/dL) × fasting glucose (mg/dL)/2]. Huang X et al concluded that the TyG- BMI has the same novel index of IR as the TyG index, which is a better indicator of IR than the HOMA-IR, and its calculation formula is TyG-BMI = TyG index × BMI [ 24 ].…”
Section: Methodsmentioning
confidence: 99%